Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.3141/2160-07
|View full text |Cite
|
Sign up to set email alerts
|

Data Collection of Freeway Travel Time Ground Truth with Bluetooth Sensors

Abstract: Accurate travel time information is essential to the effective management of traffic conditions. Traditionally, floating car data have been used as the primary source of ground truth for measuring the quality of real-time travel time provided by traffic surveillance systems. This paper introduces Bluetooth sensors as a new and effective means of data collection of freeway ground truth travel time. The concept of vehicle identification using Bluetooth signatures for travel time estimation along a section of fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(136 citation statements)
references
References 3 publications
3
133
0
Order By: Relevance
“…The total costs (in thousand dollars per mile) for a 5-year monitoring period revealed that the Bluetooth technology is the least costly method compared to the others. [9] freeway data quality for the I-95 Corridor Coalition VPP [10,11]. On this corridor, the Bluetooth technology has set the standard for quality control for outsourced traffic data [10].…”
Section: Recent Practices In Bluetooth and Crowdsourcing Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The total costs (in thousand dollars per mile) for a 5-year monitoring period revealed that the Bluetooth technology is the least costly method compared to the others. [9] freeway data quality for the I-95 Corridor Coalition VPP [10,11]. On this corridor, the Bluetooth technology has set the standard for quality control for outsourced traffic data [10].…”
Section: Recent Practices In Bluetooth and Crowdsourcing Techniquesmentioning
confidence: 99%
“…A study by the University of Maryland demonstrates that well-placed sensors should provide a 4% detection rate for roadways of 36,000 ADT (average daily traffic) or more [11]. Young [24] showed even a 2% match rate on a roadway of 100,000 ADT would provide more than enough hits to accurately generate mean travel times in 5 min intervals.…”
Section: Comparative Study In the City Of Calgarymentioning
confidence: 99%
“…The DCUs that have been reported in the literature vary from commercial-off-the-shelf (COTS) laptop computers to custom-built units which may include additional capabilities, such as global positioning system (GPS) receivers and/or cellular communications modules for remote data transfer (Haghani et al, 2010;Haseman et al, 2010;Quayle et al, 2010).…”
Section: Bluetooth Based Travel Time Data Collection Systemmentioning
confidence: 99%
“…Further investigation focusing on the use of cellular network data for inferring real-time mobility information has been conducted through surveys and data classication identifying the advantages and limitations of this method. Particularly, a discussion on the ways to increase the accuracy of known cellular positioning techniques through a traffic congestion estimation service application and studying the trajectory of several thousand of anonymous mobile phone users are found in [20,21] A new promising technology has been proposed in the traffic and urban planning community based on the interception of Bluetooth Media Access Control (MAC) addresses for the monitoring of traffic conditions that will open new measurement possibilities [22,23,18,2,5,16]. The uniqueness of the detected MAC addresses makes the Bluetooth technology particularly appropriate to monitor the mobility conditions.…”
Section: Related Workmentioning
confidence: 99%